Contestation of Human Rights Values and the Protection of Women within the Mak-Dijuk Siang Tradition - Nurnazli, Nurnazli; Akmansyah, Muhammad Akmansyah (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2025)
Problem statement: Issues pertaining to women's protection rights have ignited social debate within the framework of the mak dijuk siang tradition. This tradition, upheld by the indigenous people of Lampung, forbids divorce and conveys the moral message that marriage is sacred, noble, and honourable, thus necessitating its preservation until death separates the couple. Objective: This study seeks to investigate the underlying reasons for the conflicting values associated with the mak dijuk siang tradition among the indigenous Lampung community, as well as to evaluate the relevance of this tradition in the heterogeneous social context of the indigenous Lampung populace. Methods: A qualitative approach was employed for this study. Primary data were collected through interviews with a diverse range of informants, including community leaders, traditional leaders, and community members from the sub-districts of Anak Tuha, Gunung Sugih, and Bumi Ratu Nuban in Central Lampung Regency. Theories of justice and gender served as the analytical framework for data analysis. Results: The findings indicate that the prevailing social reality, which prioritises the protection of women and human rights, has led to a debate between traditional and contemporary values concerning the mak dijuk siang tradition. The middle ground in this value debate advocates for a dialectic between the principles of justice and equality in gender relations, grounded in human rights. Conclusion: The fact that women are seeking divorce through the Religious Court in an area with strong traditional ties to this practice demonstrates that the tradition is no longer uniformly upheld. This study advocates for the local government to continue recognising and promoting local customs that possess positive values for family resilience.